1982
DOI: 10.3758/bf03204268
|View full text |Cite
|
Sign up to set email alerts
|

Kinesthetic aspects of mental representations in the identification of left and right hands

Abstract: Kinesthetic aspects of mental representations of one's own hands were investigated. Line drawings showed a human hand in one of five versions, in which finger position and wrist rotation varied; each version occurred as a left and as a right hand, and could appear in anyone of eight directions in the picture plane. The subject was required to make quick judgments of whether a left or a right hand was represented, under three conditions of head tilt (left, upright, right). Reaction time varied systematically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
169
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(191 citation statements)
references
References 11 publications
(15 reference statements)
17
169
1
4
Order By: Relevance
“…Deagentivized gestural simulation, however, is still constrained by anatomical restrictions of the gesturing hand. The internalization process then further reduces these constraints stemming from the execution of gestures, though it may not completely remove such constraints (Sekiyama, 1982). Consequently, once the motor strategy goes through both deagentivization and internalization, it becomes much freer from the constraints of the physical world.…”
Section: Deagentivization and Internalization Of The Motor Strategymentioning
confidence: 99%
“…Deagentivized gestural simulation, however, is still constrained by anatomical restrictions of the gesturing hand. The internalization process then further reduces these constraints stemming from the execution of gestures, though it may not completely remove such constraints (Sekiyama, 1982). Consequently, once the motor strategy goes through both deagentivization and internalization, it becomes much freer from the constraints of the physical world.…”
Section: Deagentivization and Internalization Of The Motor Strategymentioning
confidence: 99%
“…In the task, participants are asked to identify a picture as being that of a left or a right hand. In general, people find it easier to mentally rotate body parts in ways that actual body parts can be easily rotated than in ways that would be awkward to perform physically (see Cooper and Shepard, 1975;Sekiyama, 1982;Parsons, 1987;Parsons, 1994). It has been shown recently that the same constraints apply to the mental manipulation of images of objects that are commonly manipulated with the hands, such as a screwdriver (C. de'Sperati and P. Viviani, pers.…”
Section: Mental Image Transformation and Motor Actionmentioning
confidence: 99%
“…Mental rotation of human body parts, especially hands, has been found to differ essentially from mental rotation of abstract objects [13,17]. Using a handedness paradigm in which participants had to decide if a displayed hand was a right or left one, Parsons [13,14] showed that RTs were not only influenced by the rotation angle of the hand stimulus but also by the implicit awkwardness of the displayed hand position.…”
Section: Introductionmentioning
confidence: 99%